Capacitance Value Analysis of Composites of Activated Cashew Shells Charcoal and Iron Sand - Anas, Muhammad; Mongkito, Vivi Hastuti Rufa; Napirah, Mardiana; Fayanto, Suritno; Takda, Amiruddin; Ariefka, Reza (Department of Physics, Sebelas Maret University, 2022)
This study aims to determine the use of iron sand extract and cashew nut shell activated charcoal in the capacitor manufacturing process and determine the effect of grain size on the capacitor capacitance with electrodes from a composite of iron sand extraction and activated charcoal from cashew nutshells. The sample preparation of cashew nutshell activated charcoal was carried out by carbonation and activation methods at a temperature of 700 0C and continued by extracting iron sand. The results of the iron sand extract were then crushed using a mortar, followed by varying the mass fraction of iron sand starting at 40%, 60%, and 80% for each particle size (60 mesh, 100 mesh, and 200 mesh). Then composite the iron sand extract and activated charcoal mixed for 4 hours, and added 0.7 mL of LiNO3 1M solution. The analysis showed that the highest specific capacitance was found in the 200 mesh grain size, namely 0.0695 F/g.